E-commerce adoption in South African businesses - S. De Klerk; J. Kroon (South African Journal of Business Management, 2005)
The modern economy is an ever-changing environment and businesses need to adapt to maintain competitive advantages and secure profits. Trade and communication barriers have faded leading to a more global and international environment. Technological advances, such as computer innovation and networks, changed the face of economic trade and play an important role in the global and electronic marketplace. Electronic commerce (e-commerce) is a low-cost way of conducting economic activities, as well as, building global business partnerships to interchange information through interconnected networks.The current awareness of the e-commerce adoption amongst the respondents in South African businesses are the focus of this article and the results of an empirical study that incorporates on-line businesses that offer products or services to consumers.A large practical significance was found on the importance and role of technology as a competitive advantage in business, especially in marketing, expert knowledge, increasing sales, enhancement of relationships and the saving of time. The most important reasons for e-commerce and international trade included profit (86 percent), access to strategic markets (64 percent) and international association by means of relationships (61 percent).
Keywords: 650